Análise da utilização de abrigos termo-higrométricos alternativos para pontos fixos - Valin Jr, Marcos de Oliveira (2015)
The standardization of data collection instruments is critical to the quality of the microclimate studies. Due to financial constraints and specific needs, many sensors, shelters and alternative systems the standards are developed, based on experience and creativity of researchers. The aim of this study is to analyse the thermo-hygrometric performance Micrometeorological shelters of different alternative materials for data collection at fixed points.There fore, the methodology is to build five types of shelters, installed in the open to ensure the same environment for the study, and evaluated the performance of variable term-hygrometric, ease of execution, materials and tools used, and costs involved.. The results showed that the shelters of the vertical type and the ice cream pot does not demonstrate efficient to collect data at fixed points, especially if used during the day. As for the other types, with plastic plates, pvc pipe horizontally and wooden house, proved to be viable alternatives for performance, fitting analyse where will be used to determine which one best fits because the horizontal depends on already know sense of wind direction, the wood of the available space due to its size and weight and the dishes depends on the availability of plastic plates in white. It is possible to also conclude that the term-hygrometric performance is not only associated to the material used, but also to its form.